Being Mimicked Increases Prosocial Behavior in 18‐Month‐Old Infants. Issue 5 (14th March 2013) - Carpenter, Malinda; Uebel, Johanna; Tomasello, Michael
Abstract : Most previous research on imitation in infancy has focused on infants' learning of instrumental actions on objects. This study focused instead on the more social side of imitation, testing whether being mimicked increases prosocial behavior in infants, as it does in adults (van Baaren, Holland, Kawakami, & van Knippenberg, 2004). Eighteen‐month‐old infants ( N = 48) were either mimicked or not by an experimenter; then either that experimenter or a different adult needed help. Infants who had previously been mimicked were significantly more likely to help both adults than infants who had not been mimicked. Thus, even in infancy, mimicry has positive social consequences: It promotes a general prosocial orientation toward others.